Uma análise comparativa de métodos aproximativos baseados em smoothed particle hydrodynamics para animação de fluidos - Barbosa, Charles Welton Ferreira (2013)
Animations of fluids, such as water or smoke, are used to add details to virtual games or films. Various methods exist for simulating fluids using particle systems, including the Smoothed Particle Hydrodynamics (SPH) method. The SPH method is a good choice for simulating fluids for its easy description and implementation. This work describes some methods based on SPH for general fluid simulation, and for the interaction between fluids and solids. These methods are analysed and compared on their realism, and a few weak points of each method are presented. This analysis may be used for the creation of better methods based on SPH, and for the realistic animation of fluids